Source, distribution, and transformation of dissolved and particulate organic matters in Qinzhou Bay, Northern Beibu Gulf - Cai, Shangjun; Wang, Chao; Zhu, Qingmei; Lao, Qibin (Frontiers in Marine Science, 2023)
Dissolved and particulate organic matter (DOM and POM) provide two reduced carbon pools of considerable size in coastal ecosystems, and they are closely linked. Currently, the integrated study concerning both the DOM and POM is limited, preventing a deep understanding of the interaction between them in the coastal region. In April 2021, thirteen surface seawater samples were collected in the offshore region of Qinzhou Bay, the northern Beibu Gulf. DOM samples were characterized using dissolved organic carbon (DOC) analysis, UV-visible, and fluorescence spectroscopy techniques. POM was determined for the particulate organic carbon and nitrogen (POC and PN) and isotopic composition (δ13C and δ15N). The poor relationships between DOC, colored and fluorescent DOM, and salinity suggest that the conservative mixing of water masses and in situ biological processes jointly dominate the distribution of DOM. A high C/N ratio of 17, POC/chlorophyll a ratio (253 ± 112), and depleted δ13C (-25.7 ± 1.6‰) confirmed that POM is highly degraded and is mainly from allochthonous input, with the contribution of 35% for the terrigenous organic matter and freshwater phytoplankton, respectively. The total organic carbon (DOC plus POC) was correlated positively with humic-like peak M, revealing the transformation from labile DOM and POM to refractory DOM components. The in situ production efficiency of peak M in offshore waters of Qinzhou Bay is one order of magnitude higher than that in inland waters and open oceans, with a large positive shift of the regression between it and temperature, suggesting the joint regulation of high temperature and sufficient labile substrate. High levels of TOC and humic-like FDOM indicate the mass coexistence of organic carbon with different reactivities, highlighting the large potential for photochemical and microbial degradations in the future.